2011
DOI: 10.1002/hep.24247
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of primary sclerosing cholangitis: A systematic review and meta-analysis

Abstract: Incidence studies of primary sclerosing cholangitis (PSC) are important for describing the disease's burden and for shedding light on the disease's etiology. The purposes of this study were to conduct a systematic review of the incidence studies of PSC with a meta-analysis and to investigate possible geographic variations and temporal trends in the incidence of the disease. A systematic literature search of MEDLINE (1950MEDLINE ( -2010 and Embase (1980Embase ( -2010 was conducted to identify studies investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
132
2
15

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(158 citation statements)
references
References 78 publications
2
132
2
15
Order By: Relevance
“…According to a recent meta-analysis, its incidence was 0.77 per 100,000 person-years (1). It is a rare disease and seems to occur at lower frequencies in Asia and Southern Europe than in America and Northern Europe (2).…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent meta-analysis, its incidence was 0.77 per 100,000 person-years (1). It is a rare disease and seems to occur at lower frequencies in Asia and Southern Europe than in America and Northern Europe (2).…”
Section: Introductionmentioning
confidence: 99%
“…PSC predominantly occurs in people aged between 37 and 43 years 2) . Its epidemiological charcterisics lead to a higher disease prevalence in the fourth and fifth decades of life.…”
Section: Discussionmentioning
confidence: 99%
“…Its epidemiological charcterisics lead to a higher disease prevalence in the fourth and fifth decades of life. A meta-analysis of data included from eight studies in Europe and North America reported that only one patient aged more than 84 years was diagnosed as having this disease 2,3) ; however, Japan is the only country that reported a second peak of incidence in the sixth decade of life. In its latest revision, the study found that 3 of 388 patients with PSC were older than 80 years 4) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatobiliary manifestations are much more commonly associated with ulcerative colitis (UC) than Crohn's disease (CD) [4,5]. The pathogenesis of hepatobiliary manifestations associated with UC may be related to liver gut interplay such as in primary sclerosing cholangitis (PSC), PSC/autoimmune hepatitis (AIH) overlap and IgG4 associated cholangitis (IAC).…”
Section: Introductionmentioning
confidence: 99%